(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Advertising is one form of presenting non-personal communication about ideas, goods and services offered by producers with the intention of influencing consumers to buy the products offered, also advertising can state the existence of a brand and persuade consumers to buy it. For this reason, advertisements must contain messages that are attractive and easily understood by buyers. Attractive advertisements are usually supported by Endoser, so that all messages conveyed can be understood by consumers. For that endoser selection is not an easy and cheap thing. Therefore, this study aims to determine how consumers respond to the credibility of the endoser used by Wardah cosmetics, and how consumers respond to the Wardah cosmetic brand image on consumer purchasing decisions. The method used in this research is a survey method, as well as descriptive and verification research methods. Data collection method, by distributing questionnaires directly to consumers who use Wardah cosmetics. The data analysis tool used is multiple regression. The results showed that the Endoser credibility variable could positively and significantly influence consumer purchasing decisions. Likewise, the brand image variable can also influence consumer purchasing decisions in Wardah cosmetics in a positive and significant way